A primer for best practices in tissue preparation for bioanalysis. (November 2012) - Kemper, Christopher J; Koetzner, Lee; Koleto, Michael
Analysis of drugs, biomarkers and their metabolites in tissue samples has always been an important aspect of the drug-development process. In the last decade, significant improvements in equipment and processes have made handling such samples far more efficient, with higher precision, accuracy and ruggedness. The purpose of this paper is to provide a primer for best practices of tissue analysis, including brief but specific tutorials on basic principles and laboratory operation. Included will be a discussion of what to consider when designing a study, tools available to make appropriate pre-study decisions, approaches for tissue acquisition and extraction, sample processing methods, and tips on creation of standards and QCs. We will offer some practical advice to help scientists who have good analytical skills, but are not experienced in tissue analysis to quickly start their own analyses with the minimum amount of time, labor and cost.